2015
DOI: 10.1051/0004-6361/201525805
|View full text |Cite
|
Sign up to set email alerts
|

A steady-state supersonic downflow in the transition region above a sunspot umbra

Abstract: We investigate a small-scale (∼1.5 Mm along the slit), supersonic downflow of about 90 km s ). Consequently, this implies a substantial mass flux (∼5×10 −7 g cm −2 s −1 ), which would evacuate the overlying corona on timescales close to 10 s. We interpret these findings as evidence of a stationary termination shock of a supersonic siphon flow in a cool loop that is rooted in the central umbra of the spot.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
64
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(83 citation statements)
references
References 54 publications
(105 reference statements)
17
64
2
Order By: Relevance
“…It should also be mentioned that a downflow is usually observed in chromospheric lines in plumes (Straus et al 2015;Chitta et al 2016), which might be associated with coronal rain or a siphon flow. The downflowing coronal material interacting with the dense lower atmosphere could result in heating and enhancement of the radio emission.…”
Section: Origin Of the Umbral Brightness Enhancementmentioning
confidence: 99%
“…It should also be mentioned that a downflow is usually observed in chromospheric lines in plumes (Straus et al 2015;Chitta et al 2016), which might be associated with coronal rain or a siphon flow. The downflowing coronal material interacting with the dense lower atmosphere could result in heating and enhancement of the radio emission.…”
Section: Origin Of the Umbral Brightness Enhancementmentioning
confidence: 99%
“…They interpreted the observations as cool material falling as coronal rain along thermally unstable loops. They observed fast apparent downflows in the 1400 Å slit-jaw time sequence, suggesting that the material is indeed cooler plasma at the TR temperatures, i.e., around 10 5 K. Straus et al (2015) investigated another supersonic downflow event in a sunspot above the lightbridge. They identified that the downflow components are steady for almost 80 min and show up as "satellite" lines of Si iv and O iv TR lines, redshifted by ≈90 km s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations from the Solar Optical Telescope (SOT) on board Hinode, the Interface Region Imaging Spectrograph (IRIS), and ground-based observatories such as the Swedish Solar Telescope have demonstrated coronal rain is a common occurrence (e.g. Antolin et al 2010;Antolin & Rouppe van der Voort 2012;Kleint et al 2014;Antolin et al 2015;Straus et al 2015). Coronal rain accelerates towards the solar surface at overall average values of around 80±30 m s −2 (Antolin & Rouppe van der Voort 2012), which is considerably smaller than solar gravitational acceleration, even when taking into account the effective gravity in the direction of the guiding magnetic field.…”
Section: Introductionmentioning
confidence: 99%